Collapse pressure of sandwich pipes with strain-hardening cementitious composite - Part 1: Experiments and parametric study. (March 2020) - Yang, Jiankun; Paz, Claudio M.; Estefen, Segen F.; Fu, Guangming; Lourenço, Marcelo Igor
Abstract: Combining both thermal insulation and structural strength in the core, sandwich pipes (SP) are a promising alternative for conventional single wall pipes in deep-water applications. The ultimate strength of SPs under external pressure has always been a major concern in the design process. An insightful understanding of the collapse pressure and post-buckling behavior of SPs is critical not only for safe application, but also for optimized design. This paper and its companion paper present a comprehensive study on the collapse pressure of SPs with strain-hardening cementitious composite (SHCC). Part 1 presents experiments investigating the collapse under external pressure of SPs composed of two steel tubes and the strain-hardening cementitious composite (SHCC) core. The experimental results were employed in correlation studies with the finite element model using the ABAQUS software; good agreement was reached. The proposed numerical model was used in a parametric study for simulating collapse in 6000 different practical configurations. The influence of the geometric parameters and material properties of the SP on its ultimate structural strength under external pressure and post-buckling behavior was systematically analyzed. The results revealed some interesting phenomena not previously reported. For example, assuming frictionless inter-layer conditions, the collapse pressure of an SP with an SHCC core decreases with increasing steel layer thickness. The reasons behind these phenomena were thoroughly discussed and the special behavior of an SP with an SHCC core subjected to external pressure is reported. The results developed in this paper were utilized in Part 2: A suitable prediction equation, where different equation forms are evaluated and one prediction equation is recommended for the design of an SP with an SHCC core. Highlights: Nine collapse tests of sandwich pipes subjected to external pressure have been carried out. Finite element models have been developed and validated against the experimental results. A parametric study composed of 6000 practical configurations of sandwich pipes has been conducted. A special collapse mechanism of SHCC sandwich pipes has been reported.